THE ANALYSIS STUDY OF TECHNICAL EFFICIENCY OF PRODUCTION FACTORS APPLICATION ON YARN PRODUCTION - Maydina Khumairoh CahyaGusti; Dody Setyadi; M Nahar (Politeknik Negeri Semarang, 2018)
This study aims to find out the influence of production factors) to the yarn production output at PT Subah Spinning Mills and to find out the technical efficiency level of yarn production factors usage in PT Subah Spinning Mills. The data type which used is the secondary. The time series data used in this research in months is from January 2015 to December 2017, there were 36 series (months). The analysis tools in this study are multiple linear regression and efficiency test. Based on the data processing result, machine work (X2) and the quantity of raw materials (X3) have positives influence to the yarn production output in PT Subah Spinning Mills, while the number of labor (X1) has a negative effect to the yarn production output in PT Subah Spinning Mills. The technical efficiency level of raw materials usage and the machine work were efficient respectively; it means that the raw materials and machine usage in PT Subah Spinning Mills had been classified in the technically efficient category. For the labors factor, the technical efficiency level of the labors usage is inefficient, in order to that, the research recommend the company to put more investment on the machine factors in hope it increasing the amount of yarn production at PT SUBAH SPINNING MILLS. Based on the results of return to scale (RTS) with a value of less than 1, the number of return to scale (RTS) is in decreasing return, which means that if there is an additional production factors, the additional production output will have a less proportion than the previous production.